Tensions Impacting Student Success in a Rural Community College - Karen R. Hlinka; Deronda Mobelini; Terri Giltnre (Journal of Research in Rural Education, 2015)
This article describes a qualitative study examining factors infl uencing the decision-making processes of traditional-age students living in rural, southeastern Kentucky as they progress toward acquiring a bachelor's degree using the community college as a steppingstone. Specifi cally, this study explored students' perspectives of the factors that serve as barriers and as sources of encouragement, impacting decision making at critical steps of students' academic pathways. Our research team divided this project into three key transition points: (a) high school seniors' decisions to attend a community college as a means to acquire a bachelor's degree, (b) community college students' decisions that promote persistence to the transfer point, and (c) community college students' decisions in choosing a specifi c transfer university. Three areas of confl icting demands that impact students' decision making about academics and place them at risk for long-term success emerged: (a) a need for one-on-one attention and support vs. a need for self-reliance, (b) the push of family encouragement vs. a pull of family responsibilities, and (c) a desire to stay in the region vs. a desire to leave. Recognition of these tensions can guide efforts of community college leaders to help students, shaped by their Appalachian culture and other defi ning traits, to build the skills necessary to complete this leg of their educational journeys.